If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(3m+4)=3(4m+17)
We move all terms to the left:
5(3m+4)-(3(4m+17))=0
We multiply parentheses
15m-(3(4m+17))+20=0
We calculate terms in parentheses: -(3(4m+17)), so:We get rid of parentheses
3(4m+17)
We multiply parentheses
12m+51
Back to the equation:
-(12m+51)
15m-12m-51+20=0
We add all the numbers together, and all the variables
3m-31=0
We move all terms containing m to the left, all other terms to the right
3m=31
m=31/3
m=10+1/3
| b^2=164 | | 7-d12=41 | | -2x+(-9x+45)1=-10 | | ⎼7n+5=⎼16 | | (45-9x)1/2=x-5 | | x+0.5=7/4 | | 7x+21=11x+55 | | 7x+3=11x-55 | | b^2=5,184 | | 3a-3=2(a+1)+8a+4 | | 5=-4x+1=x=1 | | b^2=2304 | | 360=((5x+3)+(127)+(88)+(10x+7) | | p^2+2=11 | | b^2=1,225 | | X²-4x+16=0 | | f/3+7=6 | | 0.5q+1.4=2.2 | | 12x+4=68 | | √10-3x=x+6 | | |3x-7|=17 | | 2x^2+x+10=5 | | 2 | | 2 | | ⎼5(3x⎼8)=⎼45 | | 3(1/3x-5=9-2x) | | 5k+12°=7k-16° | | b^2=3136 | | 5a+14=3(a+2)= | | 72=-8s | | 5a+14=3(a+2= | | 3c+5=62 |